Surface crack growth subject to bending and biaxial tension-compression (Fracture and Structural Integrity, 2015)
Fatigue surface crack growth and the in-plane and out-of-plane constraint effects are studied through experiments and computations for aluminium alloy D16T. Subjects for studies are cruciform specimens under different biaxial loading and bending central notched specimens with external semi-elliptical surface crack. Both the optical microscope measurements and the crack opening displacement (COD) method are used to monitor and calculate both crack depth and crack length during the tests. The variation of crack growth rate and surface crack paths behaviour is studied under cyclic pure bending and biaxial tension-compression fatigue loading. This work is centered on the relations between crack size on the free surface of specimen considered configurations, COD and aspect ratio under different fatigue loading conditions. For the experimental surface crack paths in tested specimens the T-stress, the local triaxiality parameter h, the out-of-plane TZ factor and the governing parameter for the 3D-fields of the stresses and strains at the crack tip in the form of In-integral were calculated as a function of aspect ratio by finite element analysis to characterization of the constraint effects along semi-elliptical crack front. The plastic stress intensity factor approach is applied to the fatigue crack growth on the free surface of the tested bending and cruciform specimens as well as the deepest point of the semi-elliptical surface crack front. As result fatigue surface crack paths or crack front positions as a function of accumulated number of cycle of loading are obtained.
Keywords: Surface crack; Biaxial loading; Crack growth